Chlorogenic Acid Content of Local Robusta Coffee at Variations of Roasting Temperature - Misto, M; Lestari, N P; Purwandari, E (Department of Physics, Faculty of Mathematics and Natural Sciences, 2022)
The roasting process has become the most necessary post-harvest handling process to be awarded in controlling coffee quality. In this research, the effect of roasting temperature has been investigated to the chlorogenic acid content on pure robusta coffee of local varieties and its mixture with soybeans as a parameter to control the quality. The temperature of roasting had variated at 195°C, 215°C, 225°C, 230°C, and 240°C. The chlorogenic acid contents have been obtained based on their maximum absorbances measured by a UV-Vis spectrophotometer at 290 nm wavelength range. The increase in roasting temperature reduces the chlorogenic acid levels because some have turned into melanoidin compounds. To increase the weight of Robusta coffee and change the taste of coffee, soybeans have been added as a coffee mixture. The results of the study were then extended to the observation of coffee quality on the content of chlorogenic acid it produces. The addition of soybeans by 10% can increase the chlorogenic acid content at a roasting temperature of 230°C around 5.12%, and there will be a decrease when the temperature is lowered. The addition of soybeans with a mass fraction of 20% of the total amount of coffee has increased the absorbance due to other antioxidant substances from the soybeans. The results of this study are expected to add insight to the public about the temperature required for the roasting process to obtain quality coffee with chlorogenic acid content that is still present after the roasting process.